TANGGUNG JAWAB INDONESIA SEBAGAI NEGARA PESERTA KONVENSI MENGENAI PENGHAPUSAN SEGALA BENTUK DISKRIMINASI TERHADAP PEREMPUAN DALAM MENANGANI PERKAWINAN ANAK - Samitha Andimas Putri; Hasim Purba; Suhaidi Suhaidi; Yefrizawati Yefrizawati (UNES Law Review, 2023)
Child marriage still occurs in Indonesia, even though Law No. 16/2019 has increased the minimum age for getting married from 16 year old for the bride specified in Article 7, paragraph 1 and 19 year old for the groom to 19 year old for both of them. Indonesia is the country which participates in the Convention of Elimination of All Types of Discrimination Against Women as it is specified in Article 16, paragraph 2 which reads : “the betrothal and the marriage of a child shall have no legal effect, and all necessary action, including legislation, shall be taken to specify a minimum age for marriage and to make the registration of marriages in an official registry compulsory.” Indonesia is also the country which participates in Beijing Declaration and Platform for Action in which there is the 12th of critical areas of concern : one of them is the elimination of all types of discrimination towards girls. Indonesia also participates in Sustainable Development Goals in which one of them is Target 5.3 the elimination of all harmful practices, such as child marriage